2017
DOI: 10.1002/biot.201600520
|View full text |Cite
|
Sign up to set email alerts
|

The self‐sufficient P450 RhF expressed in a whole cell system selectively catalyses the 5‐hydroxylation of diclofenac

Abstract: Abbreviations: ALA, aminolevulinic acid; BM3, cytochrome P450 from Bacillus megaterium; cdw, cell dry weight; cww, cell wet weight; HPLC, high--performance liquid chromatography; IMAC, immobilised metal affinity chromatography; IPTG, isopropyl β--D--1--thiogalactopyranoside; IR, infrared; MS, mass spectrometry; NADPH, nicotinamide adenine dinucleotide phosphate; NMR, nuclear magnetic resonance; NSAID, non--steroidal anti--inflammatory drug; P450, cytochrome P450 monooxygenase; RhF, cytochrome P450 from Rhodoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
0
41
0
1
Order By: Relevance
“…A range of activity was observed that includes demethylation, epoxidation, hydroxylation and sulfoxidation. Previously, P450‐RhF has been shown to possess a good activity towards diclofenac ( 1 ) and produce the human metabolite 5‐hydroxydiclofenac ( 2 ) . In this study, P450‐AT, AX, JT and TT all displayed better conversions (>85 %) to the hydroxylated product than RhF (63 %) under the screening conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A range of activity was observed that includes demethylation, epoxidation, hydroxylation and sulfoxidation. Previously, P450‐RhF has been shown to possess a good activity towards diclofenac ( 1 ) and produce the human metabolite 5‐hydroxydiclofenac ( 2 ) . In this study, P450‐AT, AX, JT and TT all displayed better conversions (>85 %) to the hydroxylated product than RhF (63 %) under the screening conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The P450 concentration determined by CO binding was obtained using cell‐free lysates, the plots of which are shown in Figure A and include that of P450‐RhF for comparison. Each of the P450s from this study displayed a greater thermal stability than RhF, which was encouraging given the previous issues with the stability of P450‐RhF . P450 AT and JT showed modest improvements from RhF, whereas AX, TB and TT showed significant improvements with increases in T 50 of greater than 15 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, insect P450s could also be deployed as industrial enzymes for the production of fine chemicals and pharmaceuticals that cannot be produced economically by total chemical synthesis [31] or for the development of new processes based on bioelectrocatalysis [32]. Finally, they could be used for remediation purposes, such as the removal of pesticide residues and other xenobiotics from wastewater and the environment [33].…”
Section: Insect P450s and Their Potential Applicationsmentioning
confidence: 99%